Development of numerical simulation method for melt relocation behavior in nuclear reactors: validation and applicability for actual core structures - Susumu YAMASHITA (The Japan Society of Mechanical Engineers, 2017)
In order to precisely investigate molten core relocation behavior in severe accidents, we have been developing the detailed and phenomenological numerical simulation code named JUPITER for predicting the molten core behavior with melting and solidification based on computational fluid dynamics (CFD) including the three-dimensional multiphase thermal-hydraulic simulation models. In order to treat complicated core structures, e.g., boron carbide (absorber), stainless steel (control rod, fuel support structure, etc.), Zircaloy (channel box and fuel cladding) and to deal with complicated melt relocation behaviors, high accuracy, efficient, stable and robust numerical schemes are implemented. In this paper, in order to evaluate the validity and applicability of the JUPITER for actual core structures, we perform the preliminary melt relocation analysis in the control rod and fuel support piece and also verify the validity of the JUPITER regarding the melt relocation and solidification processes by the fundamental numerical problem and the experimental analysis. As a result, the preliminary analysis showed that multicomponent melt flow and its melt and solidification were stably worked in the melt relocation simulation. In the validation analysis, the numerical results were in the reasonably agreement with experimental results. Therefore, it was confirmed that the JUPITER has a potential to calculate the core melt relocation behavior in RPVs.